2023
DOI: 10.1177/03635465231152186
|View full text |Cite
|
Sign up to set email alerts
|

A Knitted PET Patch Enhances the Maturation of Regenerated Tendons in Bridging Reconstruction of Massive Rotator Cuff Tears in a Rabbit Model

Abstract: Background: Although nondegradable synthetic grafts for bridging reconstruction of massive rotator cuff tears (MRCTs) have shown satisfactory clinical outcomes, their function and details on graft-tendon healing and enthesis regeneration have not been fully studied. Hypothesis: The knitted polyethylene terephthalate (PET) patch as a nondegradable synthetic graft could provide sustained mechanical support, facilitating enthesis and tendon regeneration in the treatment of MRCTs. Study Design: Controlled laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…However, we did not observe any breakage or ruptures in our scaffolds, suggesting that before collagen fibers fully mature, the elastomer core with its excellent biomechanical strength, suture retention value, could sufficiently and permanently support the dynamic loading strain during the tendon healing phase and prevent early tendon retear or scaffold failure after surgery. It is worth noting that in a clinical setting, nondegradable devices, including PET patch (nondegradable synthetic graft), suture anchors ( e.g ., polyether ether ketone; PEEK) and sutures ( e.g ., high molecular weight polyethylene or FiberWire®), are routinely used and not removed after surgery [ 23 , 65 , 66 ]. However, even though they can reinforce the mechanical properties, their application is limited due to the poor tenogenic-bioactivity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not observe any breakage or ruptures in our scaffolds, suggesting that before collagen fibers fully mature, the elastomer core with its excellent biomechanical strength, suture retention value, could sufficiently and permanently support the dynamic loading strain during the tendon healing phase and prevent early tendon retear or scaffold failure after surgery. It is worth noting that in a clinical setting, nondegradable devices, including PET patch (nondegradable synthetic graft), suture anchors ( e.g ., polyether ether ketone; PEEK) and sutures ( e.g ., high molecular weight polyethylene or FiberWire®), are routinely used and not removed after surgery [ 23 , 65 , 66 ]. However, even though they can reinforce the mechanical properties, their application is limited due to the poor tenogenic-bioactivity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, various tendon substitute/scaffolds have been developed to provide mechanical augmentation for tendon repair [ 22 ]. These include degradable biomaterials such as polycaprolactone (PCL), polylactic acid (PLA), and poly( l -lactide) (PLLA), as well as nondegradable materials like polyethylene terephthalate (PET) patch [ 23 , 24 ]. Despite these diverse approaches, a singular approach has yet to achieve complete functional repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al investigated the potential of a knitted PET patch as a nondegradable synthetic graft for bridging reconstruction of MRCTs in a rabbit model (Figure 3B,C). [59] The knitted PET patch was compared to an autologous Achilles tendon graft in terms of graft-bone interface scores, tendon maturation, and biomechanical properties at various postoperative time points. Histological analysis revealed that the PET patch promoted fibrocartilage formation, chondrocyte ingrowth, and Sharpey-like fiber formation at 12 weeks.…”
Section: Petmentioning
confidence: 99%
“…Reproduced with permission. [ 59 ] Copyright 2023, SAGE. D) Preparation for a 3‐layer fascia latae‐ligament‐fascia lata graft: the sandwich graft.…”
Section: Application Of Nondegradable Polymer Synthetic Materials In ...mentioning
confidence: 99%
“…Tissue engineering approaches have been explored to enhance the repair of RCT, with a particular focus on the appropriate formation of different tissue zones. Synthetic biomaterials, including polycaprolactone (PCL), polyethylene terephthalate and polyurethane, have been extensively utilized in animal models of RCT. , Biomaterial scaffolds created by three-dimensional (3D) printing have often been cocultured with mesenchymal stem cells (MSCs), treated with growth factors (GFs), and then transplanted into the rotator cuff to promote tendon-to-bone healing . MSCs or MSC-derived constructs with scaffolds have also been applied for tendon-to-bone healing. …”
Section: Introductionmentioning
confidence: 99%